Contrasting Effects of Predation Risk and Copper on Copepod Respiration Rates. (10th August 2020) - Lode, Torben; Heuschele, Jan; Andersen, Tom; Titelman, Josefin; Hylland, Ketil; Borgå, Katrine
Abstract: Natural biotic and anthropogenic stressors can interact to alter contaminant toxicity. Energetic restrictions are potential mechanisms causing this pattern. To identify processes underlying observed effects of predation risk and copper (Cu) on delayed copepod age at maturity, we examined how these 2 stressors affect respiration rates. We tested 2 very different copepod species: the large, pelagic calanoid Calanus finmarchicus and the small, semibenthic harpacticoid Tigriopus brevicornis . Adult individuals were exposed for 12 h to the treatments: predation risk, Cu (23 µg L −1 ), combined predation risk and Cu (23 µg L −1 ), or control. Oxygen concentrations were monitored continuously. The 2 species differed in their responses. We found no clear effects of either stressor in C. finmarchicus . In T. brevicornis, predation risk increased respiration rates, whereas Cu alone had little impact. In contrast, combined exposure to predation risk and Cu interacted to reduce respiration rates to less than expected. We further observed an effect of sex because female‐biased T. brevicornis replicates were more sensitive to both predation risk (increased respiration rates) and Cu exposure (reduced respiration rates). The present study provides further evidence that predation risk can interact with copepod responses toward Cu exposure. Interactive effects of biotic stressors ought to be considered to improve future marine environmental monitoring. Environ Toxicol Chem 2020;39:1765–1773. © 2020 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Abstract : Contrasting exposure effects on copepod respiration.